1976
DOI: 10.1177/030006057600400403
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Clinical Evaluation of a New Topical Steroid “Halcinonide” and Hydrocortisone in Steroid-Responsive Dermatoses

Abstract: Fifty patients with symmetrical, bilateral lesions of psoriasis, eczematous dermatitis, atopic dermatitis, or neurodermatitis participated in a double-blind paired comparison study in which 0-1% halcinonide (in a cream formulation containing also neomycin and nystatin) was applied to the lesions on one side of the body and 1% hydrocortisone cream to those on the opposite side for two to three weeks. The number of excellent responses to therapy showed the halcinonide combination to be significantly superior (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…16,19,20 Eight trials provide no baseline comparison data. 2,[7][8][9]13,[21][22][23] The amount of topical steroid used during the study period was generally not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19,20 Eight trials provide no baseline comparison data. 2,[7][8][9]13,[21][22][23] The amount of topical steroid used during the study period was generally not reported.…”
Section: Resultsmentioning
confidence: 99%
“…25 One study that evaluated a variety of steroid-responsive dermatoses, found no significant difference in global outcome for atopic dermatitis (n = 4) when comparing 0AE1% halcinonide with neomycin plus nystatin vs. 1% hydrocortisone cream in a within-patient study (left ⁄right comparison). 21 One study comparing hydrocortisone butyrate plus mupirocin with hydrocortisone butyrate or vehicle ointment in 337 children and adults found no significant difference in Eczema Area and Severity Index (EASI) scores at the end of treatment (MD )1AE08, 95% CI )2AE51 to 0AE35). 15 Another study compared 3% tetracycline plus 0AE1% triamcinolone with 0AE1% triamcinolone in 44 adults with moderate ⁄severe atopic eczema and found no significant difference in SCORing of Atopic Dermatitis (SCORAD) at the end of treatment (MD )0AE40, 95% CI )10AE39 to 9AE59).…”
Section: Clinically Uninfected or Unspecified Eczemamentioning
confidence: 99%
“…Four trials [ 33 - 36 ] published before 2000 and included in one Cochrane review [ 8 ], were not present in the GREAT database. All four trials were returned in the search strategy for the Cochrane systematic review [ 8 ] and so they were not found exclusively through hand searching.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the missing trials [248][249][250][251][252] most likely do not appear in the GREAT database owing to differences between the inclusion criteria of the review and the GREAT database, or their interpretation. The inclusion criteria for the GREAT database are broad and were designed to encompass all the RCTs of eczema treatment in relation to clinical benefits and harms.…”
Section: Discussionmentioning
confidence: 99%
“…Three trials [248][249][250] did not fit the GREAT database inclusion criteria primarily owing to not giving an adequate description of randomisation having occurred.…”
Section: Assessment Of the Trials Missing From The Great Databasementioning
confidence: 99%